HUBUNGAN TINGKAT PENGETAHUAN PEKERJA SEKSUAL KOMERSIAL TERHADAP DETEKSI DINI KANKER SERVIKS DI KAFE BELAWAN - FAHRUL ROZI; RIRI ARISANTY SYAFRIN LUBIS (LP2MTBM MAKARIOZ, 2022)
Cervical cancer is a disease characterized by uncontrolled cell growth and abnormal cell spread. The primary cause of cervical cancer is chronic infection with Human Papilloma Virus (HPV) types 16 and 18.Cervical cancer has several risk factors, Age >35 years, low Socioeconomic status, low education level, young age for firtd sexual intercourse, having more than one partner. Meanwhile, in Indonesia, cervical cancer is 23.4 per 100,000 population with an average death rate of 13.9 per 100,000 population. Objective: To determine the relationship between the level of knowledge of commercial sex workers on early detection of cervical cancer at the LG Belawan cafe. This study is a descriptive analytic study with a cross sectional design and data collection using a total sampling technique. The result of this research 32 respondents (100%) did the Pap Smear test and 0 (0,0%) respondents did not take the Pap Smear test. From the data analysis obtained P = 0,001 (P <0.05), this indicates that there is a significant relationship between the level of knowledge of commercial sex workers on early detection of cervical cancer